Pest categorisation of Davidsoniella virescens. (19th December 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Plant Health (PLH) performed a pest categorisation of Davidsoniella virescens, a well‐defined and distinguishable fungal species of the family Ceratocystidaceae. The species was moved from the genus Ceratocystis to the genus Davidsoniella following a revision of the family. The former species name Ceratocystis virescens is used in the Council Directive 2000/29/EC. The pathogen is regulated in Annex IIAI as a harmful organism whose introduction into the EU is banned on plants (other than fruit and seeds) and wood (including wood which has not kept its natural round surface) of Acer saccharum, originating in the USA and Canada. The fungus is native to eastern North America and causes symptoms mainly on A. saccharum, but also on Liriodendron tulipifera . The fungus is also reported as a saprotroph on various hardwood species. The pest could enter the EU via wood, plants for planting and cut branches. Hosts and favourable climatic conditions are widespread in the EU. The pest would be able to spread following establishment through sap‐feeding insects, root grafts and movement of infected wood and plants for planting. The pest introduction could have impacts on Acer spp. and L. tulipifera trees in the EU, by causing wilting, yellowing and the development of small leaves, as well as dieback of branches and, eventually, the death of trees. Avoiding damaging trees (as wounding facilitates infection of the fungus) and maintaining healthy trees (as tree stress facilitates the disease) are available measures to reduce impacts. The main knowledge gaps concern (i) the biology and epidemiology of the pathogen (including the saprotrophic form), (ii) the role of insect vectors for entry and spread, and (iii) the susceptibility of Acer spp. either native to or more recently established in Europe. The criteria assessed by the Panel for consideration as potential quarantine pest are met. For regulated non‐quarantine pests, the criterion on the pest presence in the EU is not met.